How Much Do Households Dislike Local Density? And Do Developers Fully Consider Their Preferences? Evidence from a Policy Change in Singapore - Eric Fesselmeyer; Haoming Liu; Louisa Poco (Institute of Labor Economics (IZA), 2021)
This paper measures how much households dislike density in their immediate surroundings. Using transaction and administrative data in Singapore, and exploiting the introduction of a regulation that restricted the number of housing units for certain land lots, we find that households do indeed discount density: a 10% increase in within-development density decreases price per square meter by up to 4%. Further, we find that the mean price per square meter of the average development increased by 1 to 3% after the regulation was introduced, while the amount of built-up space remained constant. The increase in total revenue suggests that developers may underestimate the externality caused by density. Our results are particularly relevant during the lockdowns and social distancing of the coronavirus pandemic.
Keywords: R20; R21; R38; 330; land-use policy; regulation; density; externalities